THE DYNAMICS OF HORTICULTURAL FARM NUMBERS IN DIFFERENT ECONOMIC SIZE CLASSES AND CHANGES IN THEIR INCOME IN 2007-2017 - Maryla Bieniek-Majka; Marta Guth (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2020)
The aim of this study is to determine changes in the structure of horticultural farms in EU countries in the years 2007-2017 and their incomes and determine the share of subsidies of the Common Agricultural Policy in the income of horticultural farms in studied groups. Horticultural farms from the European Union Farm Accountancy Data Network (EUFADN) of all EU countries were surveyed. A dynamic analysis of the structure of farm numbers in particular groups of economic size (ES6) was carried out, and then the average change in income and the share of subsidies in income within these groups in 2007 and 2017 were presented. As a result of the conducted research, changes in the number of horticultural farms in various groups of economic size were taken into account and the assumptions concerning the decreasing scale of fragmentation of horticultural farms were confirmed by a decrease in the number of the economically weakest groups and an increase in the number of medium and large farms. It was noted that, in the studied groups, the strongest income growths concerned farms with medium or high economic strength, which may mean that income had a significant impact on the process. Moreover, it results from the conducted research that existing institutional solutions additionally supported the tendency to reduce the scale of fragmentation of horticultural farms in the EU-12 due to the fact that the shares of subsidies were higher in groups with higher economic strength.